B.120 !!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Answer:
somone in my class is literally a new York rat
Step-by-step explanation:
Answer:
slope = -1/3, y-intercept (0, -3), x-intercept (-9 , 0)
Step-by-step explanation:
3 - x = 3(y + 4)
3 - x = 3y + 12
3y = 3 - x - 12
3y = -x -9
y = -1/3 x - 3
slope = -1/3
when x = 0 (y-intercept)
y = -1/3 × 0 - 3
y = -3
y-intercept (0, -3)
when y = 0 (x-intercept)
0 = -1/3 x - 3
1/3 x = -3
x = -9
x-intercept (-9 , 0)
Answer:
option a
![log\frac{x^{5} }{(x-8)^{6} }](https://tex.z-dn.net/?f=log%5Cfrac%7Bx%5E%7B5%7D%20%7D%7B%28x-8%29%5E%7B6%7D%20%7D)
Step-by-step explanation:
Given in the question an expression
5logx - 6log(x-6)
To solve this question we will apply two of the logarithm property
1) power rule
alogx = log![x^{n}](https://tex.z-dn.net/?f=x%5E%7Bn%7D)
log
- log![(x-8)^{6}](https://tex.z-dn.net/?f=%28x-8%29%5E%7B6%7D)
2) substraction rule
The log of a quotient is the difference of the logs
loga (x/y) = loga x - loga y
![logx^{5}- log(x-8)^{6}](https://tex.z-dn.net/?f=logx%5E%7B5%7D-%20log%28x-8%29%5E%7B6%7D)
log![\frac{x^{5} }{(x-8)^{6} }](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B5%7D%20%7D%7B%28x-8%29%5E%7B6%7D%20%7D)
The plus two is the y intercept so your point is (0,2) from there you go up one and right two and again from where you ended bc that’s the slope and from the y intercept you can go down one left two and again to continue the line